E-114 Predictors of poor outcome after successful mechanical thrombectomy of anterior circulation large vessel occlusions within 6 hours of symptom onset. (22nd July 2019) - Mohammaden, M; Stapleton, C; Brunozzi, D; Atwal, G; Alaraj, A
Abstract : Introduction: Successful recanalization is a significant predictor of a good clinical outcome after mechanical thrombectomy (MT). However, some patients have a poor clinical outcome even with complete revascularization. Objective: We aimed to study the clinical, imaging, and procedural factors that predict a poor clinical outcome (90-day modified Rankin Scale ≥ 3) in patients with anterior circulation large vessel occlusion (LVO) who undergo successful MT within 6 hours of symptom onset. Patients and methods: We performed a retrospective review of all patients who underwent MT within 6 hours of symptom onset for an anterior circulation LVO at our institution between May 2016 to June 2018. Poor outcome was defined as a modified Rankin Scale equal or more to three at 90 days. Results: A total of 56 patients met criteria for inclusion in this study. A poor outcome occurred in 31 (55.4%) patients. On univariate analysis, compared to patients with good clinical outcomes, patients with poor outcomes had higher mean NIHSS scores on presentation (23.3 vs. 13.8, P <0.001), were more likely to have internal carotid artery (ICA) occlusions (38.7% vs. 8%, P =0.008), and had a higher incidence of distal clot migration (DCM) after MT (48.4% vs. 8%, P =0.028). Age, gender, other baseline clinical characteristics, the method of revascularization, and incidence of hemorrhagic transformation did not differ between the two cohorts. Using multivariate regression analyses, baseline NIHSS score, site of occlusion, and the presence of DCM remained significant predictors of a poor clinical outcome at 90 days ( P =0.001, P =0.026, and P =0.04, respectively). Conclusion: Baseline NIHSS score, ICA occlusion, and DCM are independent predictors of a poor outcome after MT for anterior circulation LVO performed within 6 hours of symptoms onset. All values are presented as the number of patients (n) and percentage (%) unless indicated otherwise. Boldface type indicates statistical significance. Disclosures: M. Mohammaden: None. C. Stapleton: None. D. Brunozzi: None. G. Atwal: None. A. Alaraj: 1; C; NIH. 2; C; Cerenovus.